SUBJECTIVE DIMENSIONS OF SOCIAL MOBILITY AND NATIONAL CHARACTER (Modern American Journal of Social Sciences and Humanities, 2026)
This article studies the impact of the subjective factor of social mobility on national character. It is revealed that national character increases through vocational training. It is studied that subjective dimensions of social mobility are important in the formation of national character.